SUBSTITUSI TEPUNG BUNGKIL KEDELAI DENGAN TEPUNG DAUN LAMTORO DAN PENGARUHNYA TERHADAP EFISIENSI PAKAN DAN PERTUMBUHAN IKAN NILA - Titin Kurniasih; Rosmawati Rosmawati (BERITA BIOLOGI, 2013)
The high cost of fish feed is a main problem in aquaculture industries, and the effort to improve the cost efficiency of feed is the main focus for nutritional research program all over the world. Research is needed to identify less expensive and more sustainable ingredients within fish feeds, while maintaining nutritional quality equal to those based mainly on fish meal and soybean meal. Leucaena leaf meal (LLM) is a potential alternative plant protein source because of its high protein content and low cost compared to soybean meal. The Leucaena leaf was soaked in freshwater for 3 days prior to use. This study was a 60-day trial and aimed to examine the replacement of soybean meal with LLM at various level in practical feed for Nile tilapia. This trial used a Completely Randomized Design which was carried out in 15 aquarias sized of 60 x 60 x 50 cm. Triplicate group of nile tilapia (initial body weight 12,04 Â± 0,38 g fish-1 ) were fed five isonitrogenous and isocaloric feeds. The control feed was containing soybean meal, whereas in other four feeds, LLM directly replaced soybean meal with the inclusion level of 8, 16, 24 dan 31 % within the feed formulation. Result showed that the growth performance and feed efficiencies of feed containing 8, 16, 24 and 31 % LLM on the formulation were significantly lower compared to control feed. LLM was able to consumed by nile tilapia although there was a tendency of decrease of the feed consumption with the increase of LLM inclusion. It suggested that the additional treatment is needed to improve the quality of LLM, and to increase the inclusion level of LLM in feed.